Pepper Drying Using by Spouted Bed Combined with Fluidized Bed Technique - Sathapornprasath, Kitti (Srinakharinwirot University Engineering Journal, 2019)
This research is aimed at examining the dehumidification of pepper seeds by using spout fluid bed dryer. The objectives of this study were the kinetic of dehumidification of pepper seeds and the consequence of factors (i.e. temperature, velocity of hot air, drying time per power and quality used). From the results, it was found that the spout velocity of 24 m/s, the fluid velocity of 9 m/s, the temperature of 90 oC and the bed height of 10 cm are the fastest condition which can decrease moisture content of pepper seeds. The specific energy consumption (SEC) of the drying process was found at the spout velocity of 18 m/s, the fluid velocity of 9 m/s, the temperature of 90 oC and the bed height of 15 cm are 7.936 kWh/kg water, which was the minimum of the specific energy consumption of the drying process (SEC). The color of pepper seeds while using high temperature will become more red and darker than using low temperature in every condition. In addition, the destruction of pepper seeds is in range of 0.054 to 0.382 % with the spout velocity of 18 m/s, temperature of 90 oC, bed height of 10 cm and blocking of the fluid velocity, which made the destruction of pepper seeds were lowest. The velocity of fluidized was blocked cause less movement of bed which make the destruction of pepper seeds decreased.